Acute effect of post activation potentiation using drop jumps on repeated sprints combined with vertical jumps in young handball players - Al Kitani, M.; Ambussaidi, A.; Al Busafi, M.; Al-Hadabi, B.; Sassi, R. H.; Bouhlel, E.; Gmada, N. (Isokinetics and Exercise Science, 2021)
BACKGROUND: The use of post-activation potentiation (PAP) exercises at the end of the warm-up may increase muscles nerve conduction speed and per consequent improve speed, strength and explosive power performances. OBJECTIVE: To assess the effect of PAP during warm-up using vertical or horizontal drop jumps on repeated sprints performance combined with countermovement jump in young handball players. METHODS: 12 young handball players participated in this study. Participants realized 3 randomized warm-up protocols: a warm-up without PAP, a warm-up with PAP using vertical drop jumps, and a warm-up with PAP using horizontal drop jumps. After the assigned PAP protocol, the subject realized a counter movement jump as a reference value (CMJ r ), and thereafter repeated sprint tests with and without changing of direction (six maximal 2 × 12.5 m shuttle sprints and six maximal 25 m straight sprints, respectively) combined with vertical jumping. RESULTS: Horizontal drop jump during warm-up showed larger improvements in repeated sprints performance with and without change of direction for the parameters best time and mean time, compared with warm up without drop jumps (p < 0.01) and warm up with vertical drop jumps (p < 0.05). Vertical drop jump performance during warm-up induced greater gains in countermovement jump reference value in comparison with warm up without drop jump (p < 0.01), or warm up with horizontal drop jump (p < 0.01). CONCLUSION: PAP during warm-up using horizontal drop jump improves repeated sprints performance with and without changing of direction while PAP using vertical drop jump improves CMJ reference value.